Smile of the Comparatist - Ewertowski, Tomasz (Poznańskie Studia Slawistyczne, 2024)
The subject of the article is a review of Jelena Marićević Balać’s book, Ka osmehu Evrope: Savremeno srpsko, poljsko i češko pesništvo u komparativnom ključu (Toward Europe’s Smile: Contemporary Serbian, Polish, and Czech Poetry from a Comparative Perspective), which was published in Novi Sad in 2023. Marićević Balać’s book presents a collection of concise comparative studies, organized into four distinct sections, each revolving around a thematic focal point (culture; nature and culture; ecopoetics; avant-garde). Within the review, a summary of the book’s contents is provided. Additionally, the review delineates the strengths and weaknesses of Marićević Balać’s work.